LEARNING FROM THE PAST IN ORGANISING MUSIC THERAPY ACTIVITIES FOR THE GERIATRIC IN ESAN, EDO STATE OF NIGERIA. - Omoera, Osakue Stevenson; Aluede, Charles Onomudo (Voices: A World Forum for Music Therapy, 2010)
There are so many bugaboos associated with aging all over the world. While in the western world efforts are constantly being made to establish old peoples’ homes and nursing homes for geriatric purposes, the desired attention is yet to be drawn to this concept in Nigeria. Nigerian communities which used to be known for communal lifestyle seem to have jettisoned it as a result of acculturation. Today, the aged live with their kinsmen in the various societies without attention given to them; rather, they are seen as sources of threats and more often threatened to have evil hands in the death younger contemporaries in the society. This paper surveys the use of music for geriatric purposes in the previous epochs in Esan and suggests a continuum of this practice so that fruitful years could be added to the lives of the aged in Esan.